EFEKTIVITAS MULTIMEDIA INTERAKTIF PADA MATERI SISTEM PERNAPASAN MANUSIA MATA PELAJARAN IPA TERHADAP HASIL BELAJAR SISWA KELAS VIII SMPN 1 LUNANG - Nensy Purziana; Fetri Yeni J; Novrianti; Rahmi Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this research is based on the fact that students' learning outcomes in this topic are still relatively low. This is caused by the teaching method still being conventional, such as lecturing, without the support of media that can concretely and interactively visualize biological processes. As a result, students face difficulties in understanding abstract concepts such as the mechanism of gas diffusion in the alveoli, as well as the structure and function of the human respiratory organs.This study employs a quantitative approach with a pre-experimental research type and a One Group Pretest-Posttest design. The research sample consisted of eighth-grade students selected using purposive sampling techniques. The research instrument was a multiple-choice test consisting of 25 items, administered twice—before (pretest) and after (posttest) the implementation of learning using interactive multimedia. The collected data were analyzed using descriptive and inferential statistics to observe the differences in student learning outcomes before and after the treatment.The results of the study indicated a significant increase in posttest scores compared to pretest scores. This suggests that the use of interactive multimedia is effective in improving students’ learning outcomes on the topic of the human respiratory system. Interactive multimedia is considered capable of presenting material in a more engaging, visual, and communicative manner, allowing students to more easily grasp complex and unseen concepts. In addition, this media also enhances students’ motivation, active involvement, and independence during the learning process. Based on these findings, it can be concluded that interactive multimedia is an effective learning tool to improve student outcomes, especially in science subjects that require conceptual understanding and visualization of biological processes. Therefore, it is highly recommended that interactive multimedia be integrated into the learning process at schools to improve overall education quality.